Multi-Cultural Considerations for Counselling First Nations Clients - Nuttgens, Simon A.; Campbell, Allan J. (Canadian Journal of Counselling and Psychotherapy, 2010)
Despite evidence that First Nations people experience a disproportionate degree of mental health concerns relative to other Canadians, many within this population do not access Western-based mental health services. In this article we extend a socio-political and historical rationale for attending to key cultural differences when working with First Nations clientele. These cultural differences are situated within the three commonly held domains of multicultural competence: self-awareness, knowledge of the other, and therapeutic practice.